Preventive Therapy for Contacts of Drug-Resistant Tuberculosis - Kherabi, Yousra; Tunesi, Simone; Kay, Alexander; Guglielmetti, Lorenzo (Pathogens (Basel), 2022)
Preventing the progression of a drug-resistant tuberculosis (DR-TB) infection to disease is an important pillar of the DR-TB elimination strategy. International guidelines have recently proposed fluoroquinolones for tuberculosis preventive therapy (TPT) in DR-TB contacts, although the available evidence is low quality. The pooled data from small observational studies suggest that a fluoroquinolone-based TPT is safe, effective and cost-effective as a preventive treatment in DR-TB contacts. Three clinical trials are currently ongoing to generate higher quality evidence on the efficacy of levofloxacin and delamanid as a DR-TB preventive therapy. Additional evidence is also needed, regarding TPT treatment in fluoroquinolone-resistant-TB contacts, patient and health care worker perceptions on DR-TB preventive therapy for contacts, and the service delivery models to increase DR-TPT access. This state-of-the-art review presents the current literature on TPT for contacts of DR-TB cases, focusing on the available evidence and international guidelines.